Quality of life assessed 6 months after hospitalisation for acute heart failure: an analysis from REPORT‐HF (international REgistry to assess medical Practice with lOngitudinal obseRvation for Treatment of Heart Failure). (12th May 2022) - McNaughton, Candace D.; McConnachie, Alex; Cleland, John G.; Spertus, John A.; Angermann, Christiane E.; Duklas, Patrycja; Tromp, Jasper; Lam, Carolyn S.P.; Filippatos, Gerasimos; Dahlstrom, Ulf; Dickstein, Kenneth; Schweizer, Anja; et al.
Abstract : Aims: Recovery of well‐being after hospitalisation for acute heart failure (AHF) is a measure of the success of interventions and the quality of care but has rarely been quantified. Accordingly, we measured health status after discharge in an international registry (REPORT‐HF) of AHF. Methods and results: The analysis included 4606 patients with AHF who survived to hospital discharge, had known vital status at 6 months, and were enrolled in the United States of America, Russian Federation, or Western Europe, where the Kansas City Cardiomyopathy Questionnaire (KCCQ) was administered. Median age was 69 years (quartiles 59–78), 40% were women, and 34% had a left ventricular ejection fraction (LVEF) <40%, and 12% patients died by 6 months. Of 2475 patients with a follow‐up KCCQ, 28% were 'alive and well' (KCCQ >75), while 43% had poor health status (KCCQ ≤50). Being 'alive and well' was associated with new‐onset AHF, LVEF <40%, younger age, higher baseline KCCQ, country, and race. Associations were similar for increasing health status, with the exception of country and addition of comorbidities. Conclusion: In this international global registry, health status recovery after AHF hospitalisation was highly variable. Those with the best health status at 6 months were younger, had new‐onset heart failure, and higher baseline KCCQ; nearly one‐third of survivors were 'alive and well'. Investigating reasons for changes in KCCQ after hospitalisation might identify new therapeutic targets to improve patient‐centred outcomes. Abstract : ( A ) Kansas City Cardiomyopathy Questionnaire overall summary score (KCCQ‐OSS) at baseline, 6 months, and 12 months. ( B ) Forest plot of characteristics associated with being 'alive and well' at follow‐up. LVEF, left ventricular ejection fraction; HF, heart failure. *Multivariable logistic regression.